2017
DOI: 10.1103/physrevd.95.044024
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cosmological parameters by the simulated data of gravitational waves from the Einstein Telescope

Abstract: We investigate the constraint ability of the gravitational wave (GW) as the standard siren on the cosmological parameters by using the third-generation gravitational wave detector: the Einstein Telescope. The binary merger of a neutron with either a neutron or black hole is hypothesized to be the progenitor of a short and intense burst of γ rays, some fraction of those binary mergers could be detected both through electromagnetic radiation and gravitational waves. Thus we can determine both the luminosity dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
222
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(226 citation statements)
references
References 42 publications
(97 reference statements)
0
222
0
4
Order By: Relevance
“…Einstein Telescope: Various studies have shown that further increase in sensitivity is required for performing precise gravitational wave astronomy, testing of general relativity and improving our understanding of exotic phenomenon like the equation of state and tidal deformability of neutron stars [14,67,[105][106][107]. The Einstein Telescope is a proposed next-generation European gravitational wave observatory [62][63][64] with sensitivity an order of magnitude higher than advanced LIGO and extending down to 1 Hz.…”
Section: Future Detectors and Networkmentioning
confidence: 99%
“…Einstein Telescope: Various studies have shown that further increase in sensitivity is required for performing precise gravitational wave astronomy, testing of general relativity and improving our understanding of exotic phenomenon like the equation of state and tidal deformability of neutron stars [14,67,[105][106][107]. The Einstein Telescope is a proposed next-generation European gravitational wave observatory [62][63][64] with sensitivity an order of magnitude higher than advanced LIGO and extending down to 1 Hz.…”
Section: Future Detectors and Networkmentioning
confidence: 99%
“…This is the origin of the fact that coalescing binaries are 'standard sirens', i.e. their waveform allows a direct reconstruction of the luminosity distance to the source [167][168][169][170][171][172][173][174][175][176][177][178][179]. In GR, for a cosmological model with energy density ρ DE (z), the relation between luminosity distance and redshift is…”
Section: Tensor Perturbations In Grmentioning
confidence: 99%
“…In principle, all values of ι ∈ [0 • , 180 • ] are possible. It is pointed out that the maximal effect of inclination angle on the SNR is a factor of 2 [39,44]. Here we only consider the simplified case where the binary's orbital plane is nearly face on, hence the amplitude A is independent of the polarization angle ψ.…”
Section: Gws As Standard Sirensmentioning
confidence: 99%
“…Following Ref. [39], we assume that d L is uncorrelated with that of other parameters and then double the uncertainty of d L calculated from the Fisher matrix as the upper limit of instrument error on d L , i.e.,…”
Section: Gws As Standard Sirensmentioning
confidence: 99%
See 1 more Smart Citation